Government Purchases and Relative Prices in a Two-Country World. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
The effects of government expenditures on interest rates, terms of trade, and real exchange rates are examined in a three-good (importables, exportables, nontradables), two-country, intertemporal, optimizing model. Temporary spending increases (on tradable or nontradable goods) may raise or lower the world return on internationally traded bonds and may improve or worsen the current account of the country undergoing the fiscal expansion. The results are shown to differ substantially from those obtained in models employing a higher degree of commodity aggregation. The determinants of the comovement between the terms of trade and the real exchange rate are also examined.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet